Stability of Linear Delay Differential Equations A Numerical Approach with MATLAB - Breda, Dimitri (Springer, 2015)
Many problems of growing interest in science, engineering, biology, and medicine are modeled with systems of differential equations involving delay terms. In gen eral, the presence of the delay in a model increases its reliability in describing the relevant real phenomena and predicting its behavior. Besides, the introduction of history in the evolution law of a system also augments its complexity since, opposite to Ordinary Differential Equations (ODEs), Delay Differential Equations (DDEs) represent infinite dimensional dynamical systems. Thus their time inte gration and the study of their stability properties require much more effort, together with efficient numerical methods...